Kardinale deugden gekerstend de vier kardinale deugden vanaf Ambrosius tot het jaar 1000. - Bovendeert, Jasmijn 1975-; Raedts, Peter S. J. 1948-; van Gemert, G.C.A.M.; Bejczy, István Pieter; Radboud Universiteit Nijmegen (Nijmegen F&N Boekservice, 2007)
This study examines the use of the four cardinal virtues of prudence (prudentia), fortitude (fortitudo), temperance (temperantia), and justice (iustitia) in the writings of the Church Fathers Ambrose, Jerome, and Augustine, and in early medieval texts (ca. 375-1000). These four virtues were introduced by Plato (Politeia 427a sq.), incorporated in the Stoa, and assimilated in Christian moral teachings in patristic times. This study focuses on two genres in which the four virtues are mentioned during Late Antiquity and the Early Middle Ages: texts on moral subjects and biblical commentaries. These texts are investigated in seven chapters. In addition this study focuses on the way the cardinal virtues were christianised from Ambrose up to the year 1000.
Proefschrift Radboud Universiteit Nijmegen
Met samenvatting in het Engels
Keywords: Cardinal virtues; 248.145.2 -- Kardinale deugden; Theses